LPS Stimulation Induces Small Heterodimer Partner Expression Through the AMPK-NRF2 Pathway in Large Yellow Croaker (Larimichthys crocea) - Jianlong Du (Frontiers Media S.A., 2021)
The mall heterodimer partner (SHP) plays an important regulatory role in mammal inflammation. The main objective of this study was to investigate the response of SHP to inflammatory stimulation and its underlying mechanism. The shp gene from large yellow croakers, was cloned, and this gene is mainly expressed in the liver and intestine. Lipopolysaccharide (LPS) stimulation induced the mRNA expression and protein level of SHP in macrophages of large yellow croakers. Overexpression of SHP significantly decreased mRNA expression of tnfα, il-1β, il-6 and cox2 induced by LPS treatment in macrophages. LPS stimulation increased the phosphorylation level of Adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK) in macrophages. AMPK inhibitor treatment significantly decreased the expression of SHP induced by LPS while AMPK activator significantly increased the expression of SHP. The nuclear factor-erythroid 2-related factor 2 (NRF2) increased the promoter activity of SHP in large yellow croakers and the level of nuclear NRF2 was increased by LPS stimulation and AMPK activation. NRF2 inhibitor treatment significantly decreased mRNA expression of shp induced by LPS and AMPK activator. In conclusion, LPS can induce SHP expression by activating the AMPK-NRF2 pathway while SHP could negatively regulate LPS-induced inflammation in large yellow croakers. This study may be benefit to the development of immunology of marine fish and provide new ideas for inflammation-related diseases.